Masjid dan Ruang Spiritualitas Bagi Difabel: Observasi Kritis terhadap Masjid-masjid Populer di Yogyakarta - Asparina, Atropal (UIN Sunan Kalijaga Yogyakarta, 2019)
Every religious person has an equal space for spirituality to exercise, feel, and express his beliefs, but then this faces obstacles such as social class, gender bias, and especially disability. This research elaborates on the concept of an ideal-inclusive Islamic spirituality space in the Qur'an and Hadith, and also the spirituality space for people with disabilities in popular mosques in Yoyakarta. This study uses a hermeneutic approach to the Qur'an and Hadith and descriptive-analytic methods through critical observation and interviews with managers of popular mosques in Yogyakarta. As a result, the concept of spiritual space in the Koran, Hadith, even early Islamic history, has been very 'friendly' for people with disabilities, although historically this effort has been constrained by social factors such as majority-minorities, budget facilities, traditions and established culture. Therefore, the writer tries to classify the mosque into: a public mosque, a mosque towards a disabled person, a mosque with a disability awareness, and a mosque that is friendly to people with a disability.